Interface between management control systems and strategy and performance measures in a family business - Oro, Ieda Margarete (2019)
This study aimed to analyze how the interface occurs between the management control systems (MCSs) and the strategy and performance measures in a family business, from the perspective of Contingency Theory. The relevance of the theme lies in understanding how the use of the managerial levers from the Levers of Control (LOC) model (Simons, 1995) is perceived by the senior management of a family business in the interface with the strategy and performance measures. In terms of its impact in the area, this article broadens the field of research that uses the LOC model together with strategy and performance measures in family businesses. The research methodology used combined methods, operationalized by the case study procedure. The content analysis was performed using coded categories based on the literature and selected passages from the interviews, observation, and documents, by means of qualitative analysis software. As a result, it was observed that the family management designed by the controlling owner, with an entrepreneurial vision, working together (father and sons), and the organizational values of the family unit (belief systems), showed particularities of the family-business duality that contributed to the implementation of the strategy and the use of performance measures. It is also inferred that the two systems (diagnostic controls and interactive controls) are complementary in the organization and that the “customized control” produced by the integrated management system is an adjustment of the MCS to the contingencies in order to enable the interface with the strategy and performance measures. The study revealed that the family values present in the management take form in the belief systems that shape the use of the MCSs and in the strategic behavior of the organization, which is an element that is barely discussed in Simons (1995) and opens up room for new research.